Status Perceptions of Management “Peers” - Balk, Walter L. (Academy of Management Journal, 1969)
It is often said that management people at the same official level on the organizational chart often do not consider themselves as equal in status. This reports an investigation of perceived status between such ?equal-appearing? managers. The findings indicate that higher management should increase its awareness of the status implications associated with task complexity.